Influence of medium pH on surfactant synthesis by acinetobacter calcoaceticus IMV B-7241 on ethanol - Konon, Anastasia; Antoniuk, Svitlana; Chebotaryova, Ksenia; Parfenyuk, Sergey; Pirog, Tatiana (My University, 2012)
It was stated that during the cultivation of Acinetobacter calcoaceticus IMV B-7241 in the medium with ethanol the pH maintenance at 6–7 was accompanied by the 2-fold increase of the concentration of synthesized metabolites with surface-active properties. Under such conditions of cultivation the qualitative composition of the synthesized neutral, phospho- and glycolipids was almost unchanged compared with the cultivation without pH regulation.
Keywords: кафедра біотехнології і мікробіології